Targeting Vascular Changes in Lesions in Multiple Sclerosis and Experimental Autoimmune Encephalomyelitis - J. Karlik, Stephen; A. Roscoe, Wendi; Patinote, Cindy; Contino-Pepin, Christiane (Central Nervous System Agents in Medicinal Chemistry, 2012)
What is the origin of the complex vascular changes that exist in the CNS lesions of Multiple Sclerosis (MS)? From the beginning of the study of the pathological changes in MS in the 19th century, lesions were seen to be associated with veins. On a microscopic level, there have been numerous pathological changes to these vessels including altered structure and permeability, fibrinolysis, iron-related alterations and collagen deposition. Vascular changes in inflammatory conditions outside the CNS are well documented and we hypothesize that angiogenesis (the generation of new blood vessels from existing) is an integral process of lesion development and spread in MS. We demonstrated similar vascular abnormalities in MS and in the animal model, EAE. We measured the increase in angiogenesis-related genes in EAE and review herein the effectiveness of chemical inhibitors of angiogenesis (SU5416, thalidomide and several derivatives). We postulate that interference with angiogenesis provides a suitable non-immunological target for investigation in MS.
Keywords: CNS